Enabling Institutional Control for Project Risk Management in the Context of Digital Transformation - Ahmed Hamzah Abbas; Zaid Aed Mardan; Hayder Neamah Kadhim (Indonesian Journal of Law and Economics Review, 2026)
General Background: Rapid digital technological advancement has transformed business environments, increasing complexity and challenging traditional internal control systems. Specific Background: The integration of digital systems and artificial intelligence has reshaped management practices, requiring alignment between institutional control and project risk management. Knowledge Gap: Conventional control frameworks remain inadequate in addressing risks within dynamic digital transformation contexts. Aims: This study evaluates the activation of institutional control supported by digital systems in managing project risks. Results: Findings reveal a statistically significant relationship, with institutional control explaining 16.7% of variance in project risk management outcomes and strong agreement on ethical leadership and risk identification practices. Novelty: The study introduces an integrated framework combining institutional control, digital systems, and performance evaluation tools. Implications: Results emphasize the need for adaptive control frameworks, strengthened digital governance, and improved organizational coordination to support effective risk management in evolving digital environments. Highlights:• Strong Statistical Linkage Identified Between Control Activation and Risk Handling Outcomes• Leadership Ethics and Structured Identification Processes Show High Organizational Agreement• Integrated Framework Combining Governance Tools and Digital Infrastructure Proposed Keywords: Digital Transformation, Institutional Control, Project Risk Management, IT Governance, Performance Evaluation.